2022
DOI: 10.21608/ejhm.2022.242765
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance Profiles of Carbapenem-Resistant Klebsiella Pneumoniae Isolated from Tertiary Care Hospital, Egypt

Abstract: Background: Carbapenem-resistant Klebsiella pneumoniae (CR-Kp) dissemination is a major healthcare problem due to its limited treatment options.Objective: This study aimed to determine the prevalence and antimicrobial resistance profile of hospital infections caused by CR-Kp in Al-Ahrar Teaching Hospital. The study was conducted through the period from January 1, 2021 to December 31, 2021. Patients and Methods: 650 clinical samples were collected from different ICU departments. Klebsiella pneumoniae isolates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…isolated in this study, 76.25% were XDR, 18.75% were PDR, and only 5.00% were MDR, while among E. coli isolates, 75% were XDR, 20% were MDR, and 5% showed PDR. An alarming elevated prevalence of MDR, XDR, and PDR isolates was also revealed by many up-to-date studies [20][21][22][23].…”
Section: Discussionmentioning
confidence: 78%
“…isolated in this study, 76.25% were XDR, 18.75% were PDR, and only 5.00% were MDR, while among E. coli isolates, 75% were XDR, 20% were MDR, and 5% showed PDR. An alarming elevated prevalence of MDR, XDR, and PDR isolates was also revealed by many up-to-date studies [20][21][22][23].…”
Section: Discussionmentioning
confidence: 78%
“…(9) , Febrile neutropenia only 29 (5.8%) because our retrospective study and the data of patients taken from the hospital information department and laboratory department, not all data were written in the patient's medical reports. In contrast with a study conducted (10) where 172 episodes of FN in 77 patients were evaluated 54.7% of the FN episodes were in male patients and 45.3% of the FN were female.…”
Section: Discussionmentioning
confidence: 61%
“…These carbapenemases are plasmid-mediated and can be easily disseminated in the community as well as in hospital wards conferring a great impact on public health [13] . In Egypt, many studies showed a high level of carbapenem resistance among hospital K. pneumoniae isolates [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%